The Effect of Product Quality, Brand Image, and Social Media Influencers on the Purchase Decision of Scarlett Whitening Products on Social Media Instagram in DKI Jakarta - Resti Hardini; Yunita Pratiwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of product quality, brand image, and social media influencers on purchasing decisions for Scarlett Whitening products on Instagram social media in DKI Jakarta. The source of data in this research is primary data distributed in the form of questionnaires to respondents. The population used in this study were Scarlett Whitening consumers in DKI Jakarta and a sample of 100 respondents. The sampling technique in this study used non-probability sampling with purposive sampling. The data analysis technique used in this study is the Multiple Linear regression method and hypothesis testing, processed using the IBM SPSS Version 23 application to measure the regression coefficient. This study has a multiple linear regression equation Purchase Decision = 0.167X1 + 0.372X2 + 0.475X3. Based on the results of the t-test of Product Quality, Brand Image and Social Media Influencers partially have a positive and significant effect on purchasing decisions.